Fundamentals of Engineering Heat and Mass Transfer (si units) - Sachdeva (R C) (2006)
Heat and Mass Transfer
43716a.jpg;43716b.jpg;43716c.jpg;43716d.jpg;43716e.jpg;43716f.jpg
22.5
Keywords: Heat and Mass Transfer